2022
DOI: 10.1038/s41598-022-06130-w
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of the Gram-positive fish pathogen Renibacterium salmoninarum reveals putative role of membrane vesicles in virulence

Abstract: Bacterial kidney disease (BKD) is a chronic bacterial disease affecting both wild and farmed salmonids. The causative agent for BKD is the Gram-positive fish pathogen Renibacterium salmoninarum. As treatment and prevention of BKD have proven to be difficult, it is important to know and identify the key bacterial proteins that interact with the host. We used subcellular fractionation to report semi-quantitative data for the cytosolic, membrane, extracellular, and membrane vesicle (MV) proteome of R. salmoninaru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Some studies indicated a cell wall hydrolase role in bacterial growth and division by controlling the degradation of the peptidoglycan layer in bacteria, and that are thus referred to explicitly as peptidoglycan hydrolases [ 56 , 57 ]. A recent study on Gram-positive bacteria detected proteomic enrichment of four cell wall hydrolases in OMVs and suggested the involvement of CWH in the formation of the OMV [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicated a cell wall hydrolase role in bacterial growth and division by controlling the degradation of the peptidoglycan layer in bacteria, and that are thus referred to explicitly as peptidoglycan hydrolases [ 56 , 57 ]. A recent study on Gram-positive bacteria detected proteomic enrichment of four cell wall hydrolases in OMVs and suggested the involvement of CWH in the formation of the OMV [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CWH transcript was conserved in six (highly virulent) strains with 100% sequence identity and three (low virulence strains) ( Supplementary File S3 ). As these enzymes are primarily involved in cell lysis during bacterial cell division, cell wall synthesis, development [ 63 ], and OMV formation [ 58 ], they might be crucial for bacterial survivability, which might explain the evolutionary conservation of this gene in a vast number of Fp strains.…”
Section: Resultsmentioning
confidence: 99%
“…Peptides were fractionated into eight fractions using the high pH reversed-phase peptide fractionation kit (Pierce TM Thermo Fisher Scientific) according to the manufacturer's instructions and using self-made columns as previously described [48]. Digested, dried peptides were resuspended in 300 μl of 0.1% trifluoroacetic acid and suspensions transferred onto the columns.…”
Section: Protein Processing and Mass Spectrometrymentioning
confidence: 99%
“…Intriguingly, a recent proteome study found a high abundance of p57, p22 (a second key immunosuppressive protein), and proteins implicated in bacterial adhesion in membrane vesicles of R. salmoninarum , suggesting that the membrane vesicles could play a role in the pathogen attachment and subsequent BKD development [ 58 , 59 , 60 ].…”
Section: Pathogen-centric Approachesmentioning
confidence: 99%